Analisa Ketepatan Data Pengukuran Dengan Alat Ukur Theodolite T.0 Dan GPS ( Global Posisioning System ) - Edito Dwiantoro (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2017)
Each level of the earth’s surface has a different height. Therefore, measurement of the situation and topography is important for the planning work and physical work. The important of measuring the topography and the situation as a contributing factor to the efficiency and effectiveness of a job. The high point of diffence that wiil beobtained, determinetd by the axes in the plane shown in a vertical sign measuring. Current topography measurement issues are often the topics to be consideren for the job of a plan. Elevation is one of the problems in drawing a plan of work stages. Diffrence in elevation affect the volume of a very physical job. The purpose of this study was to analyze the results of measurements of topography which will look different in height, so the difference in elevation between the measuring instrument gauges Gps ( Global Posisioning System ) and Theodolite can be optimized, making it useful for planning and as a refrence to a physical. This study uses a Gps ( Global Posisioning System ) measuring devices and measuring instruments Theodolite by performing measurements of 10 ( ten ) each STA whit its distance 50 ( fifty ) until 100 ( one hundred ) meter. STA making does not use permanent markers, but by using red paint for the singn of the measurements made with Gps ( Global Posisioning System ) measuring device are not lost. This facilitates the measurement by using a tool measure Theodolite because the measuring instrument has a point to point STA sentring these points. The data taken in each STA is the data spacing (d) optimal, elevation, coordinates and coordinates. After the data is obtained, then compared with the analytical calculation of the prevaling topography. Results of research conducted comparison elevation using Gps measuring devices and measuring instrumens Theodolite we can conclude that for accurate elevations obtained from the Gps measuring devices can not be used from the planning work and physical work for every point elevation STA produced (-) mines 1 meter (do not heve this level of accuracy of the data), it does not correspond to the actual situation on the ground. As with the Theodolite measuring devices (T.0) which as a good level of concordace data and also have a good correction. But for the distance and direction that share a common coordinate measuring device Theodolite (T.0)